Tuberculosis and the sexual and reproductive lives of women in Bangladesh - Barua, Mrittika; Driel, Francien Van; Jansen, Willy (PLOS ONE, 2022)
This article was published in the PLOS ONE [© 2018 Barua et al. This is an open access article distributed under the terms of the Creative Commons Attribution License ] and the definite version is available at: https://doi.org/10.1371/journal.pone.0201134 The Journal's website is at: https://journals.plos.org/plosone/article/citation?id=10.1371/journal.pone.0201134